How to really ruin your financial life and portfolio - Stein, Ben (Wiley, 2012)
Hilarious advice on what NOT to do with money, from financial funny man Ben Stein Everyone's searching for the secrets to financial success, but what about the best ways to lose money ...fast?! In How To Really Ruin Your Financial Life and Portfolio, bestselling author, economist, financial commentator, and media personality Ben Stein explains exactly what to do ...to go bust! The ultimate "how-NOT-to" guide, the book gives readers invaluable tips that should be avoided at all costs. Written in Stein's own inimitable style, this hilarious guide provides essential financial advice on what not to do when it comes to managing money. From reading and acting upon investing newsletters to trading on a margin, from investing in bonds to breathlessly following CNBC, and from buying stock in firms you do not understand to believing in your own genius at stock picking to keeping as little cash on hand as possible, Stein presents the rules that every would-be investor needs to know, so they can do the exact opposite and actually make money